Bulk inclusion micro‐zircon U–Pb geochronology: A new tool to date low‐grade metamorphism. (11th July 2021) - Hollinetz, M. Sophie; Schneider, David A.; McFarlane, Christopher R. M.; Huet, Benjamin; Rantitsch, Gerd; Grasemann, Bernhard
Abstract: Dating low‐grade metamorphism is challenging since such rocks commonly lack suitable target minerals for acquiring pressure–temperature–time–deformation ( P–T–t–d ) data. Herein a new geochronological method termed 'bulk inclusion dating' is applied to a chloritoid‐bearing schist from the Staufen‐Höllengebirge Nappe (SHN, Austroalpine Unit, Eastern Alps, Austria) for which Cretaceous metamorphism is imprecisely constrained. Thermodynamic modelling of the phase relations and mineral chemistry predicts the stability of the equilibrium assemblage in a P–T field between 450–490℃ and 0.5–0.7 GPa, which agrees with peak temperature constraints 490℃ derived from Raman spectroscopy of carbonaceous material. Chemical zoning of, and the zonation of inclusions within, chloritoid confirm porphyroblast growth at these conditions. High‐resolution imaging reveals thousands of minute (length: 0.1–3 µm), euhedral micro‐zircon crystals included in chloritoid porphyroblasts and in the matrix. The morphological and microstructural characteristics of micro‐zircon as well as the crystal size distributions indicate that it nucleated and grew at greenschist facies conditions most likely from a Zr‐saturated fluid. In situ laser ablation inductively coupled plasma mass spectroscopy bulk inclusion dating of metamorphic zircon in the chloritoid rim using a laser spot diameter of 120 μm yields a U–Pb age of 116.7 ± 9.1 Ma (MSWD: 1.5, n : 79). We interpret zircon precipitation and progressive coarsening coeval with chloritoid growth during prograde metamorphism and thus link the age to the late prograde part of the P–T evolution. The contribution of other U‐bearing phases (apatite, epidote, rutile) does not significantly disturb the U–Pb age. The data provide clear evidence for Early Cretaceous metamorphism in the SHN and indicates that metamorphism started at least 20 m.y. before the formation of eclogites in the Austroalpine Unit. The method introduced here allows integration between metamorphic conditions and age constraints in low‐grade metamorphic rocks and opens up new potential applications in petrochronology.